2006
DOI: 10.1051/0004-6361:20065040
|View full text |Cite
|
Sign up to set email alerts
|

Encounters of the dust trails of comet 45P/Honda-Mrkos-Pajdusakova with Venus in 2006

Abstract: Aims. We aim to investigate the dynamical fate of meteoroids ejected during past perihelion passages of comet 45P/Honda-Mrkos-Pajdusakova that intersect the orbit of Venus. Of particular interest is the possibility, borne of previous work, that a significant flux of these particles will reach the planet during early June and late August 2006, when the Venus Express spacecraft will be operating in orbit around Venus. Methods. We have simulated the generation of meteoroid trails ejected by the comet at some past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…By an interesting coincidence, from studying the orbital data of fireballs associated with the α Capricornids meteor stream in Earth's atmosphere, Hasegawa (2001) concluded that exactly our three candidate comets 45P/H-M-P, 72P/D-F , and 141P/Machholz 2-A could be associated with this meteor stream, out of six possible candidates including three additional comet and asteroid candidates. Comet 45P/H-M-P was also predicted to be the source of a meteor shower in the Venus atmosphere (Vaubaillon & Christou 2006).…”
Section: Discussionmentioning
confidence: 98%
“…By an interesting coincidence, from studying the orbital data of fireballs associated with the α Capricornids meteor stream in Earth's atmosphere, Hasegawa (2001) concluded that exactly our three candidate comets 45P/H-M-P, 72P/D-F , and 141P/Machholz 2-A could be associated with this meteor stream, out of six possible candidates including three additional comet and asteroid candidates. Comet 45P/H-M-P was also predicted to be the source of a meteor shower in the Venus atmosphere (Vaubaillon & Christou 2006).…”
Section: Discussionmentioning
confidence: 98%
“…By an interesting coincidence, from studying the orbital data of fireballs associated with the α Capricornids meteor stream in Earth's atmosphere Hasegawa (2001) concluded that exactly our three candidate comets 45P/H-M-P, 72P/D-F and 141P/Machholz 2-A, among three additional comet and asteroid candidates, could be associated with this meteor stream. Comet 45P/H-M-P was also predicted to be the source of a meteor shower in the Venus atmosphere (Vaubaillon & Christou 2006).…”
Section: Discussionmentioning
confidence: 98%
“…The method used here was developed by Vaubaillon et al (2005a,b) for use at the Earth and adapted for the Martian orbit as was done in Vaubaillon & Christou (2006) for the case of Venus. We integrate numerically the dynamical evolution of test particles initially ejected from the cometary nucleus, and identify instances where significant fluxes of stream meteoroids may be incident at Mars, both in the recent past and in the future.…”
Section: Methodsmentioning
confidence: 99%
“…Such a method (Vaubaillon et al 2005a,b) was used recently to study the evolution of dust trails ejected from comet 45P/Honda-Mrkos-Pajdusakova and characterise their encounter circumstances with Venus during the comet's close approach to that planet in 2006 (Vaubaillon & Christou 2006). …”
Section: Introductionmentioning
confidence: 99%